Reciprocal Interactions between Nematodes and Their Microbial Environments - Midha, Ankur; Schlosser, Josephine; Hartmann, Susanne (Frontiers in Cellular and Infection Microbiology, 2017)
Parasitic nematode infections are widespread in nature, affecting humans as well as wild, companion, and livestock animals. Most parasitic nematodes inhabit the intestines of their hosts living in close contact with the intestinal microbiota. Many species also have tissue migratory life stages in the absence of severe systemic inflammation of the host. Despite the close coexistence of helminths with numerous microbes, little is known concerning these interactions. While the environmental niche is considerably different, the free-living nematode Caenorhabditis elegans (C. elegans) is also found amongst a diverse microbiota, albeit on decaying organic matter. As a very well characterized model organism that has been intensively studied for several decades, C. elegans interactions with bacteria are much more deeply understood than those of their parasitic counterparts. The enormous breadth of understanding achieved by the C. elegans research community continues to inform many aspects of nematode parasitology. Here, we summarize what is known regarding parasitic nematode-bacterial interactions while comparing and contrasting this with information from work in C. elegans. This review highlights findings concerning responses to bacterial stimuli, antimicrobial peptides, and the reciprocal influences between nematodes and their environmental bacteria. Furthermore, the microbiota of nematodes as well as alterations in the intestinal microbiota of mammalian hosts by helminth infections are discussed.